Stanyajanan Mahakashaya and its Utility for Mother and Child in Breast Feeding - Kumari, Manju; Ramamurthy, A; Chaudhary, Krutika (International Research Journal of Ayurveda & Yoga, 2022)
Stanyapana (breastfeeding) is essential for new-born infants as well as for mothers. Breastmilk provides nourishment to infant that is needed for overall growth and neurological development. Human breast milk serves as a source of nutrition which is uncontaminated by environmental pathogen. Multiple immunological factors like IgA produced by the mother’s immune system are transported to infant through breast milk and are associated with a protective role against infection in children. It reduces the incidence of infantile diarrhoea, allergic/hypersensitivity diseases, and development of Type 1(insulin dependent) and Type 2 (non-insulin dependent) diabetes mellitus. In Ayurvedic classics acharya Charak has described ten herbs for improving breast milk under the name “Stanyajanana Mahakashaya” which can be utilized for mother and child’s preventive and therapeutic aspect. The purpose of this work is to present a conceptual analysis of stanyajanan mahakashaya and its utility for mother and child in breast feeding.